Discovery of pyrido[3,4-g]quinazoline derivatives as CMGC family protein kinase inhibitors: Design, synthesis, inhibitory potency and X-ray co–crystal structure - Esvan, Y; Zeinyeh, W; Boibessot, T; Nauton, L; Théry, V; Knapp, S; Chaikuad, A; Loaëc, N; Meijer, L; Anizon, F; Giraud, F; Moreau, P (Elsevier, 2016)
The design and synthesis of new pyrido[3,4-g]quinazoline derivatives is described as well as their protein kinase inhibitory potencies toward five CMGC family members (CDK5, CK1, GSK3, CLK1 and DYRK1A). The interest for this original tricyclic heteroaromatic scaffold as modulators of CLK1/DYRK1A activity was validated by nanomolar potencies (compounds 12 and 13). CLK1 co-crystal structures with two inhibitors revealed the binding mode of these compounds within the ATP-binding pocket.